2021
DOI: 10.3233/nre-210010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of robotic exoskeleton gait training during acute stroke on functional ambulation

Abstract: BACKGROUND: Stroke is a leading cause of disability resulting in long-term functional ambulation deficits. Conventional therapy can improve ambulation, but may not be able to provide consistent, high dose repetition of movement, resulting in variable recovery with residual gait deviations. OBJECTIVE: The objective of this preliminary prospective investigation is to evaluate the ability of a robotic exoskeleton (RE) to provide high dose gait training, and measure the resulting therapeutic effect on functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…The ReWalk (ReWalk Robotics, Yoknaem, Israel) was the first lower extremity device to receive Food and Drug Administration (FDA) approval in 2014, followed by the Ekso (Ekso Bionics, Richmond, CA) and Indego (Parker Hannifin, Cleveland, OH) in 2016, and the Keeogo (B-temia Inc., Quebec City, Canada) in 2020. Prior studies have demonstrated the ability of individuals with neurological disorders who have partial impairments to those who are completely non-ambulatory to walk independently in robotic exoskeletons [8][9][10][11][12][13][14][15][16][17][18][19]. Exoskeletal-assisted locomotion (EAL) has been shown to improve functional and motor recovery [8], mobility [9,10,15,16], chronic pain [20], muscle spasticity [20][21][22], cardiovascular health [13,23], bowel function [24], bladder function [21,22], and quality of life [21].…”
Section: Introductionmentioning
confidence: 99%
“…The ReWalk (ReWalk Robotics, Yoknaem, Israel) was the first lower extremity device to receive Food and Drug Administration (FDA) approval in 2014, followed by the Ekso (Ekso Bionics, Richmond, CA) and Indego (Parker Hannifin, Cleveland, OH) in 2016, and the Keeogo (B-temia Inc., Quebec City, Canada) in 2020. Prior studies have demonstrated the ability of individuals with neurological disorders who have partial impairments to those who are completely non-ambulatory to walk independently in robotic exoskeletons [8][9][10][11][12][13][14][15][16][17][18][19]. Exoskeletal-assisted locomotion (EAL) has been shown to improve functional and motor recovery [8], mobility [9,10,15,16], chronic pain [20], muscle spasticity [20][21][22], cardiovascular health [13,23], bowel function [24], bladder function [21,22], and quality of life [21].…”
Section: Introductionmentioning
confidence: 99%
“…The ReWalk (ReWalk Robotics, Yoknaem, Israel) was the first lower extremity device to receive Food and Drug Administration (FDA) approval in 2014, followed by the Ekso (Ekso Bionics, Richmond, CA) and Indego (Parker Hannifin, Cleveland, OH) in 2016, and the Keeogo (B-temia Inc., Quebec City, Canada) in 2020. Prior studies have demonstrated the ability of individuals with neurological disorders who have partial impairments to those who are completely non-ambulatory to walk independently in robotic exoskeletons [8][9][10][11][12][13][14][15][16][17][18][19]. Exoskeletal-assisted locomotion (EAL) has been shown to improve functional and motor recovery [8], mobility [9,10,15,16], chronic pain [20], muscle spasticity [20][21][22], cardiovascular health [13,23], bowel function [24], bladder function [21,22], and quality of life [21].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated the ability of individuals with neurological disorders who have partial impairments to those who are completely non-ambulatory to walk independently in robotic exoskeletons [8][9][10][11][12][13][14][15][16][17][18][19]. Exoskeletal-assisted locomotion (EAL) has been shown to improve functional and motor recovery [8], mobility [9,10,15,16], chronic pain [20], muscle spasticity [20][21][22], cardiovascular health [13,23], bowel function [24], bladder function [21,22], and quality of life [21]. These studies highlight the growing demand for wearable robotic exoskeletons to improve physical and psychological health, employment opportunities, and community integration in persons with neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that exoskeleton has a good effect on the rehabilitation of lower limbs for stroke patients. 2 In recent years, many major breakthroughs on exoskeleton have been obtained. [3][4][5][6][7] An exoskeleton driven by wire rope is proposed in 2019 8 which is used to assist people with hemiplegic.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that exoskeleton has a good effect on the rehabilitation of lower limbs for stroke patients. 2 In recent years, many major breakthroughs on exoskeleton have been obtained. 3 7…”
Section: Introductionmentioning
confidence: 99%